Tingkat Kesadaran Masyarakat Dalam Pemeliharaan Bangunan Yang Berdampak Pada Aktivitas dan Kenyamanan Rumah di Bantul - Surya Manggala Yudha Guritno (Jurnal Ilmiah Global Education, 2026)
Indonesia is highly prone to earthquakes, and many post-disaster assistance houses in Bantul suffered structural degradation due to inadequate occupant maintenance. This study aims to analyze the effect of community awareness dimensions—knowledge, attitude, behavior, and social lifestyle—on household comfort through multiple linear regression. A quantitative cross-sectional survey was conducted among 65 purposively and snowball sampled recipients of 2006 Bantul aid housing. Data were collected via a closed-ended questionnaire, validated by Pearson correlation (r > 0.175) and tested for reliability with Cronbach’s alpha (α ≥ 0.70). Classical assumptions (normality, multicollinearity, heteroskedasticity, autocorrelation) were satisfied before regression analysis. Results show that all awareness dimensions jointly explain 61.7% of comfort variance (F = 35.62; p < 0.001), with local context knowledge exerting the strongest positive influence (β = 0.41; p < 0.05). Technical maintenance variables, namely electrical and roof-load checks, had negative effects. In conclusion, enhancing technical literacy, fostering responsible attitudes, and strengthening community collaboration are essential to sustain structural function and comfort of seismic-resistant aid housing